Utilizing the Short Mood and Feelings Questionnaire to measure symptoms of depression among Vietnamese adolescents in Hanoi, Vietnam, during the COVID-19 pandemic - Vinh, Ngo Anh; Long, Nguyen Thanh; Trang, Do Thi; Trang, Le Thu; Thuy, Le Thi Thanh (Frontiers in Psychiatry, 2024)
Objective: This study aimed to measure depression among children and adolescents during the COVID-19 pandemic in Hanoi, Vietnam and its associated factors by using the Short Mood and Feelings Questionnaire (SMFQ) instrument.We conducted a cross-sectional study among students from grades 6 to 9 within two secondary schools in Hanoi, the capital of Vietnam. A structured questionnaire was used, including information about personal characteristics, perception of COVID-19, and SMFQ. Factor analysis, Multivariate logistic and Tobit regression models were used.Results: Among 2378 students, 8.8% had depressive symptoms. The mean SMFQ score was 4.5 (SD=5.0). Being female, studying in higher grades, perceived low household income, higher perceived impacts of COVID-19 on health and higher perceived impacts of COVID-19-related quarantine on life were positively associated with factors' scores, SMFQ score and depressive symptoms. Meanwhile, having better academic performance, living with parents and having higher perceived knowledge about COVID-19 were negatively associated with factors scores, SMFQ score and depressive symptoms.Conclusions: Depressive symptoms were common among secondary school students in Hanoi, Vietnam, during the COVID-19 pandemic. Tailored interventions to improve pandemic-related knowledge and family and school support should be warranted for the students to enhance their mental well-being.